Adat Se-Atorang (Local Wisdom) of the Ternate People As a Model of Anti-Corruption Education - Marasabessy, Abd. Chaidir; Utaminingsih, Sri; Pujilestari, Yulita (Jayapangus Press, 2024)
Although the local government has accommodated the advantages of local values in the Ternate region, educational institutions in the regions have not integrated the advantages of local wisdom values in learning local content. Local wisdom should not be used as a mere symbol, it needs to be integrated in order to create learning that is decorated with wisdom so that the Indonesian generation has strong mental resilience, high morals, forms commendable behavior, and grows an anti-corruption culture. The research aims to describe the customs of the Ternate people as a model of anti-corruption education and its relevance to anti-corruption principles. Descriptive-based qualitative is the choice of this research. Research data is obtained through interviews and supported by relevant documentation and journals and books. Conclusion; 1)